Sixteen Semesters of Chemistry at the University of Zürich: A Retrospective on a Formative Time - Peter Wipf (CHIMIA, 2008)
Anecdotes of a chemist's roadmap from Aargau to Zürich, Virginia, and Pennsylvania.